Indonesia’s State Identity in Global Climate Governance - Yang, Jiaolian; Niu, Zhenpeng (Journal of Theory and Practice in Economics and Management, 2025)
At a time when the world’s political and economic systems are changing and the global governance system is transforming, Indonesia has both the common identity characteristics of a developing country and a breakthrough in its pure developing country background. In global climate governance, it has shaped itself into a “maintainer” and “builder” at the domestic level, a “leader” and “coordinator” at the regional level, and an “innovator” and “connector” at the global level. This article explores what kind of identity cognition Indonesia has constructed in global climate governance, how it adjusts its multiple identities at the national, regional and global levels, and analyzes what kind of identity cognition plays a leading role in specific scenarios.